Factors Affecting Survival in Congenital Diaphragmatic Hernia: A Prospective Study at a Tertiary Center - Maryam Ghavami-Adel; Hosein Dalili; Mamak Shariat; Vafa Ghorbansabagh; Fateme Nayeri; Tahereh Esmaeilnia Shirvany; Elahe Amini; Azita Parvizizadeh (EL-Med-Pub, 2020)
Background: The outcome of congenital diaphragmatic hernia depends on associated anomalies, degree of pulmonary hypoplasia, and hypertension. We evaluated the postnatal prognostic factors which can be used to predict the outcome. Methods: This study was conducted at a tertiary center (Vali-e-Asr Hospital, Imam Khomeini Complex, Tehran, Iran) during 2013-2019. The predictors of survival were evaluated. Results: A total of 49 infants with congenital diaphragmatic hernia were born during 2013-2019. The patients' mean gestational age and weight at birth were 37.51±1.75 weeks and 2871±562 g, respectively. The mortality rate in patients with surgery (n = 41) was 31.3% and eight patients died before surgery. Mortality had significant relationships with five-minute Apgar score, peak inspiratory pressure before and after surgery, partial pressure of arterial oxygen (PaO2), and pH during first 24 hours after birth (p= 0.01, 0.001, and 0.01, respectively). The predicted and true survival rates in the patients were 66% and 52%, respectively (p= 0.001). Conclusion: Predicting survival rate after birth is remarkable but controversial. This estimate should not affect patient care and should only help parents in the process of decision-making.